Evaluation of mitogenome sequence concordance, heteroplasmy detection, and haplogrouping in a worldwide lineage study using the Precision ID mtDNA Whole Genome Panel - Strobl, Christina; Churchill Cihlar, Jennifer; Lagacé, Robert; Wootton, Sharon; Roth, Chantal; Huber, Nicole; Schnaller, Lisa; Zimmermann, Bettina; Huber, Gabriela; Lay Hong, Seah; Moura-Neto, Rodrigo; Silva, Rosane; et al. (Elsevier BV, 2019)
The emergence of Massively Parallel Sequencing technologies enabled the analysis of full mitochondrial (mt)DNA sequences from forensically relevant samples that have, so far, only been typed in the control region or its hypervariable segments. In this study, we evaluated the performance of a commercially available multiplex-PCR-based assay, the Precision ID mtDNA Whole Genome Panel (Thermo Fisher Scientific), for the amplification and sequencing of the entire mitochondrial genome (mitogenome) from even degraded forensic specimens. For this purpose, more than 500 samples from 24 different populations were selected to cover the vast majority of established superhaplogroups. These are known to harbor different signature sequence motifs corresponding to their phylogenetic background that could have an effect on primer binding and, thus, could limit a broad application of this molecular genetic tool. The selected samples derived from various forensically relevant tissue sources and were DNA extracted using different methods. We evaluated sequence concordance and heteroplasmy detection and compared the findings to conventional Sanger sequencing as well as an orthogonal MPS platform. We discuss advantages and limitations of this approach with respect to forensic genetic workflow and analytical requirements.
Keywords: Mitochondrial genome; MtDNA; Haplogroups; Phylogeny; Massively parallel sequencing; Forensic genetics